Predictive Role of Cyberbullying and Victimization on General Psychological Distress among PhD Students (Indian Journal of Extension Education, 2025)
The study examines the predictive impact of cyberbullying and cyber victimization on general psychological distress (stress, anxiety, and depression) among PhD students. A total of 250 doctoral participants in 2025 (male = 122, female = 128, age mean = 28.02, standard deviation = 2.66) from Banaras Hindu University and Aligarh Muslim University were assessed. A self-prepared demographic survey, Cyber-Bullying and Cyber Victimization Experience Questionnaire (CBVEQ-E α = .89) and depression, anxiety, and stress scale-21 (DASS-21.89) were used for the purpose. Hierarchical stepwise regression analysis was employed and revealed that cyberbullying significantly positively predicted higher levels of stress (β = 0.236, p < .001), anxiety (β = 0.261, p < .001), depression (β = 0.260, p < .001), explaining 5 to 6.3% of the variance in individual general psychological distress dimensions. Cyberbullying also emerged as a significant predictor of general psychological distress (β = 0.280, p < .001), contributing 7.1 per cent of the variance. These findings underscore the adverse effects of cyberbullying on the mental health of doctoral students due to high-pressure academic environments. The study emphasizes the need for mental health interventions, institutional support systems, and anti-bullying policies to mitigate the negative impact of cyberbullying in academic settings.